Design development and manufacture of a 4-axis laser engraving cnc machine to engrave wooden mica, watermelon and cylindrical component surfaces - Dang , Minh Phụng; Le , Hiếu Giang; Le , Sỉ Đang; Ho , Gia Nghiêm; Truong , Hoàng Đức; To , Minh Thuận (Journal of Technical Education Science, 2021)
Although the laser beam technology was introduced for ages (around 1965-1967), its application in manufacturing technology (drilling, cutting, engraving, welding, ..) has developed and become popular recently. In fact, this manufacture method can be classified as a special processing technology (non-traditional). Over the past few years in Vietnam, laser beam technology has advanced rapidly and been applied in a range of industrial fields such as mechanics, interior decoration and medicine. However, research and manufacture work on laser equipment has not been sufficient to meet the actual demand for engraving wooden mica, water melon and cylindrical component surfaces. As a result, the 4-axis CNC engraving machine based on the application of Laser has been proposed to address these issues. This paper presents the results of design development and manufacturing of a 4-axises laser engraving CNC machine, with A-axis mechanism for engraving cylindrical parts and Z axis for adjusting the gap of laser-head and work-piece automatically. The equipment applies Benbox software for running code to engrave onto the surface of mica, wooden souvenir products, watermelons and cylindrical components. In addition, this machine is used to support students and lecturers in their learning, teaching and researching activities in the “Machines and computerized numerical control” course.